Evaluation of Mail Horse-Armour - David Jones; Emma Herbert-Davies (EXARC Journal, 2022)
This study was undertaken to gain an understanding of the effectiveness of mail armour in protecting horses against arrow shot, and to assess the circumstances in which such armour might play a useful role. Since the protection given by mail is largely dependent on the thickness of the underlying padding, a preliminary step was to estimate the maximum thickness of padding that could be worn by the horse during cavalry operations. Experimental tests were then conducted by shooting arrows with reproduction medieval bodkin points at reproduction mail over various thicknesses of woven linen fabric.  It was concluded that it would not be feasible to attain complete protection against arrows by mail armour and linen padding while remaining within the carrying capacity of horses for day-long operations. The fully-armoured medieval warhorse would probably have had a very limited role. The combined effect of weight and thermal loading meant that it could only perform effectively for relatively short periods. In engagements where remounts might be at hand, such as battles and tournaments, this was not a problem. However, for chevauchée type operations, which were likely to be carried out further afield and required sustained periods of speed and endurance, it would have proved counterproductive.